Process theodicy and the life after death: a possibility or a necessity? - Vescovelli, Sofia (Nuovo Giornale di Filosofia della Religione (NGFR), 2021)
In this paper I argue for the necessity of eschatology for process thought, and against the idea that the belief in a life after death is not an essential element for this theodicy. Without reference to an eschatological dimension, a process theodicy is led to admit a consequentialist conception of divine love and goodness that is inconsistent with its notion of a responsive and participative God who loves each creature. In the world many creatures suffer atrocious evils, which destroy the value of their lives, but the process God does not redeem these sufferings in a personal post-mortem life in which the sufferers participate and can find meaning for their individual evils. In order to support my thesis, I intend to examine some difficulties in process theodicy, especially in Charles Hartshorne’s position, showing how his doctrine of objective immortality is unsatisfactory. My starting point will be some criticisms advanced by John Hick against Hartshorne and the replies made by the process philosopher David R. Griffin. I conclude by contending that process theodicy, at least in its Hartshornean version, in denying the necessity of a personal afterlife, does not provide a satisfying answer to the soteriological-individual aspect of the problem of evil, namely the problem of the individual salvation in which the individual person can find redemption and meaning for the sufferings undergone or inflicted. In the process perspective the divine love is conceived in consequentialist terms and evils suffered by the individual are merely considered a by-product or the negative side of the divine creation out of chaos.